2019
DOI: 10.1371/journal.pone.0215188
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cAMP accumulation and activity by distinct phosphodiesterase subtypes in INS-1 cells and human pancreatic β-cells

Abstract: Pancreatic β-cells express multiple phosphodiesterase (PDE) subtypes, but the specific roles for each in β-cell function, particularly in humans, is not clear. We evaluated the cellular role of PDE1, PDE3, and PDE4 activity in the rat insulinoma cell line INS-1 and in primary human β-cells using subtype-selective PDE inhibitors. Using a genetically encoded, FRET-based cAMP sensor, we found that the PDE1 inhibitor 8MM-IBMX, elevated cAMP levels in the absence of glucose to a greater extent than either the PDE3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…Lastly, PDE1 inhibition has been linked to improved insulin signaling and may have a beneficial impact on diabetes. 40 Its inhibition was also recently found to protect against proteotoxicity in mice with misfolded protein disease. 41 These effects from PDE1 inhibition are potentially relevant to various heart failure syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, PDE1 inhibition has been linked to improved insulin signaling and may have a beneficial impact on diabetes. 40 Its inhibition was also recently found to protect against proteotoxicity in mice with misfolded protein disease. 41 These effects from PDE1 inhibition are potentially relevant to various heart failure syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed that the action of A. arabica involved the closure of K-ATP channels, membrane depolarisation, the opening of voltage-dependent calcium channels, the influx of Ca 2+ and the elevation of intracellular Ca 2+ . Stimulatory effects nevertheless persisted in β cells depolarised by tolbutamide or 30 mM KCl, suggesting additional actions such as the activation of adenylate cyclase, which is supported by positive potentiation by the phosphodiesterase inhibitor, IBMX [25].…”
Section: Discussionmentioning
confidence: 94%
“…Second, PDE4 has been shown to be expressed in the rat insulinoma cell line INS-1 and primary human β-cells. However, PDE1 and PDE3, not PDE4, appear to be the primary regulators of insulin secretion and, as mentioned earlier, increased cAMP signaling resulting from PDE inhibition within β-cells should be promoting insulin release, rather than inhibiting it [ 7 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%